Microalgal metabolites as anti-cancer/anti-oxidant agents reduce cytotoxicity of elevated silver nanoparticle levels against non-cancerous vero cells. Issue 10 (October 2020) - Hussein, Hanaa Ali; Maulidiani, M.; Abdullah, Mohd Azmuddin
Abstract: Heavy metal pollution has become a major concern globally as it contaminates eco-system, water networks and as finely suspended particles in air. In this study, the effects of elevated silver nanoparticle (AgNPs) levels as a model system of heavy metals, in the presence of microalgal crude extracts (MCEs) at different ratios, were evaluated against the non-cancerous Vero cells, and the cancerous MCF-7 and 4T1 cells. The MCEs were developed from water (W) and ethanol (ETH) as green solvents. The AgNPs-MCEs-W at the 4:1 and 5:1 ratios (v/v) after 48 and 72 h treatment, respectively, showed the IC50 values of 83.17–95.49 and 70.79–91.20 μg/ml on Vero cells, 13.18–28.18 and 12.58–25.7 μg/ml on MCF-7; and 16.21–33.88 and 14.79–26.91 μg/ml on 4T1 cells. In comparison, the AgNPs-MCEs-ETH formulation achieved the IC50 values of 56.23–89.12 and 63.09–91.2 μg/ml on Vero cells, 10.47–19.95 and 13.48–26.61 μg/ml on MCF-7; 14.12–50.11 and 15.13–58.88 μg/ml on 4T1 cells, respectively. After 48 and 72 h treatment, the AgNPs-MCE-CHL at the 4:1 and 5:1 ratios exhibited the IC50 of 51.28–75.85 and 48.97–69.18 μg/ml on Vero cells, and higher cytotoxicity at 10.47–16.98 and 6.19–14.45 μg/ml against MCF-7 cells, and 15.84–31.62 and 12.58–24.54 μg/ml on 4T1 cells, respectively. The AgNPs-MCEs-W and ETH resulted in low apoptotic events in the Vero cells after 24 h, but very high early and late apoptotic events in the cancerous cells. The Liquid Chromatography-Mass Spectrometry-Electrospray Ionization (LC-MS-ESI) metabolite profiling of the MCEs exhibited 64 metabolites in negative ion and 56 metabolites in positive ion mode, belonging to different classes. The microalgal metabolites, principally the anti-oxidative components, could have reduced the toxicity of the AgNPs against Vero cells, whilst retaining the cytotoxicity against the cancerous cells. Abstract : Environmental science; Toxicology; Cell biology; Biochemistry; Heavy metals; Microalgal metabolites; Silver nanoparticles; Apoptosis; Cell-cycle; Metabolite profiling.